Implementasi Model Panting Muatan PPKN Untuk Meningkatkan Motivasi, dan Berpikir Kritis Siswa Kelas V SDN 1 Murung A Hulu Sungai Tengah - Hairunnisa Hairunnisa; Noorhapizah Noorhapizah (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was conducted because the background was low student motivation and critical thinking skills. So the aim of this research is to explain how teacher activities increase student activity, learning motivation and skills in critical thinking. Researchers used a qualitative and also quantitative approach with this type of PTK research carried out over 4 meetings. The research subjects were class V students at SDN Murung A with a total of 14 students. The results of the research show that teacher activity at the 4th meeting received very good criteria, student activity was very active, student motivation reached a percentage of 85.71% and critical thinking skills at the 4th meeting reached 85.71%.